Spinning with the Hand Spindle: An Analysis of the Mechanics and its Implications on Yarn Quality - Verhecken, André (Archaeological Textiles Review, 2013)
A qualitative analysis of the process of yarn spinning with the hand spindle is proposed. The parameters influencing the characteristics of the yarn spun are identified: they are mainly defined by the fibre, the spindle and the spinner. Consequently the spindle whorl is not the unique factor determining the quality of the yarn spun with it, as has been suggested in the archaeological and ethnological literature.